Redescription of Bythotrephes arcticus Lilljeborg, 1901 (Crustacea:Cladocera: Onychopoda) and confirmation of an independent species status of the distant Transcaucasian populations of the genus Bythotrephes Leydig - Korovchinsky, Nikolai M. (Zootaxa, 2016)
Two species of the genus Bythotrephes Leydig, B. arcticus Lilljeborg and B. transcaucasicus Behning, forming a group of close species, are redescribed on the basis of type material and other materials from Northern Eurasia. They were investigated with the application of detailed morphological analysis, including intra- and interpopulation variability and the original scheme of morphometric measurements. The lectotypes and paralectotypes of the species were selected. B. arcticus compared with other species of the genus, seem more evolutionary primitive and less specialized, judging from its large body size, comparatively short tl I, short and straight caudal process, well developed distal setae on two proximal endopodital segments of tl I, and large number of claws. B. arcticus tends to occur in small and shallow water bodies, while B. transcaucasicus was predominantly found in pelagic zone of large and deep Transcaucasian lakes. B. arcticus is probably mainly distributed along the tundra and northern forest area of the Eurasian continent and the nearest islands from Scandinavia to Eastern Siberia. Its documented easternmost locality is situated near the northern part of the Yenisei River, whereas B. transcaucasicus was recorded in the second half of 19th–first half of 20th century in three closely situated mountain lakes in Turkey, Georgia, and Armenia. The presence of B. arcticus in Northern Kazakhstan and B. transcaucasicus in the distant Transcaucasia is linked with their (or their ancestor) hypothetical displacement to the south in the period of ice ages. More recent surveys of Transcaucasian lakes have not revealed the presence of B. transcaucasicus. The rare findings of this species in the past can imply that it could also be missed in the process of collecting but, on the other hand, it cannot be excluded that B. transcaucasicus become extinct as a result of an anthropogenic or other impact on Transcaucasian lakes.